PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SD - Hadist Awalia Fauzia (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This study aims to determine differences in learning outcomes of Mathematics of primary school students usingproblem based learning model. The type of research used is the meta-analysis of research that has been donebefore. This research uses quantitative synthesis method. The purpose of this study is to determine the effect ofusing problem based learning model on elementary mathematics subjects. Data collection in this research isdone by searching journal through google scholar. Keywords used for journal search are: improving the resultsof elementary mathematics learning, problem based learning. From the model of problem based learningselected 10 research results to be analyzed further in% form. Based on the results of the analysis of 10 researchresults, it can be concluded that the learning with Problem based learning model (PBL) can improve thelearning outcomes of learners learner. Increased learning outcomes from the lowest 5% to the highest 40%, withan average of 22.9%.